Teaching methods for critical thinking in health education of children up to high school: A scoping review. - Anna Prokop-Dorner; Aleksandra Piłat-Kobla; Magdalena Ślusarczyk; Maria Świątkiewicz-Mośny; Natalia Ożegalska-Łukasik; Aleksandra Potysz-Rzyman; Marianna Zarychta; Albert Juszczyk; Dominika Kondyjowska; Agnieszka Magiera; Małgorzata Maraj; Dawid Storman; et al. (PLoS ONE)
According to the World Health Organization, the improvement of people's health literacy is one of the fundamental public health challenges in the 21st century. The key issue in teaching health literacy is to develop critical thinking skills. As health literacy and critical thinking should be developed at school age, we reviewed teaching methods or educational interventions used in empirical studies focused on the development of critical thinking regarding health and implemented by teachers in preschools, primary schools, or secondary schools. We searched seven databases (Medline, Embase, Web of Science, ERIC, ProqQuest, PsycArticles, and CINAHL) from inception to 20 September 2023 for any type of empirical studies. Due to the heterogeneity in interventions and inadequate reporting of results, a descriptive synthesis of studies was performed in addition to quantitative analysis. Of the 15919 initial records, 115 studies were included in the review. Most of the educational interventions focused on lifestyle-related health issues such as substance use, sexual and reproductive health, and nutrition. The popularity of health issues changed over time and depended on the geographical context. Six dimensions that differentiated the teaching methods were identified: central teaching component, central educator, pupils' activity level, teaching context, educational materials, and significance of critical thinking. Many educational interventions did not address the development of critical thinking skills in a comprehensive manner, and the significance of critical thinking varied greatly. Interventions in which critical thinking had high and very high significance applied mainly problem-solving methods and involved pupils' activity. The evidence on the effectiveness of the teaching methods that develop critical thinking is limited because most articles failed to provide detailed information on the teaching methods or did not examine their effects. We recommend that a checklist is developed to facilitate a detailed description of health educational interventions and thus promoting their replicability. Study registration: The protocol of the review was registered in the OSF Registries on 13 January 2022 (doi: https://doi.org/10.17605/OSF.IO/46TEZ).